Impact of Digital Media on Social-Emotional Development in Early Childhood: A Case Study at TK Kartika XX-46 Kendari - Budiarti, Erna; Yasmin Adar, Sitti (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2023)
This qualitative study explores digital media's impact on children's social-emotional development at TK Kartika XX-46 Kendari, particularly emphasizing its educational utility and influence on educators' motivation and teaching efficacy. Employing a multi-phase approach involving planning, implementation, and assessment, the research reveals that digital media positively affects children’s social-emotional growth, as evident through heightened enthusiasm and positive behaviors like empathy. The study also discovered an enhancement in educators' motivation and diversification in teaching methods. Initial limitations, such as low digital literacy among teachers and insufficient infrastructure, have been progressively mitigated through concerted efforts involving multiple stakeholders. In a broader context, these findings offer valuable implications for educational practices and public policy by laying the groundwork for future research to refine pedagogical strategies. The study's limitations include its restricted scope, which is confined to one educational institution. Future studies should investigate varied educational settings and examine the complex effects of different digital platforms on children's social-emotional development.